Lasting value lessons from a century of agility at Lincoln Electric - Maciariello, Joseph A. (John Wiley, 2000)
In its 104-year history, Lincoln Electric Company has managed to sustain its status as the world's leader in welding technology despite intense domestic and foreign competition. The company's success can be attributed to founder James Lincoln, who began adopting principles of management that empowered workers and allowed the company to change rapidly to take advantage of new opportunities. This book shows you how to duplicate these pioneering ideas and follow the brilliance of the Lincoln management system. The results of this system include happier customers, more prosperous workers, and richly rewarded shareholders.